Universalisme Dan Relativisme Budaya Dalam Penegakan Ham Terhadap Kasus Kerangkeng Manusia Dan Perbudakan Modern - Sylvia Dwi Andini (Universitas Widya Gama Malang, 2022)
Universalism and cultural relativism are two different and conflicting points of view regarding human rights, universalism has a wider scope, namely universally, while cultural relativism is more inclined towards society or the culture that exists in society. Human rights themselves prohibit all forms of slavery such as deprivation of liberty, deprivation of rights, deprivation of comfort and welfare, deprivation of honor and torture. The proof of a case of human exploitation and the finding of a human cage requires us to eliminate all forms of slavery, because slavery is an act that is very inhumane and very degrading to human dignity, especially in the case of human cages. The purpose of this article is to find out and understand universalism and cultural relativism through a case study of human rights violations in Indonesia. The research method used is a normative juridical research method. With regard to cases of human exploitation and the existence of human cages that have been proven to be torture, violence as well as degrading treatment, we must return to the existing regulations, namely Article 28 G paragraph 1 “Everyone has the right to protection for himself, his family and his family. , honor, dignity and property under their control, as well as the right to a sense of security and protection from the threat of fear to do something which is a human right. The actions taken by the inactive Langkat Regent are completely unjustified, apart from tripping over a corruption case, he also violates a person's human rights. The slavery carried out by the District Head of Langkat has clearly violated Law No. 19 of 1999 concerning the Ratification of the ILO Convention on the Abolition of Forced Labor.